Analysis of the psychological meaning of the concept science in primary and secondary school teachers: an approach from an experience of continuous - Aguilar Correa, Cristián Manuel (2019)
The aim of the study was to analyze the psychological meanings of current teachers participating in a process of continuous training. The intentional, non-probabilistic sample was composed of graduate students of the Natural Sciences program (Valdez, 2005), 46 teachers—23 of them elementary education teachers and 23 secondary teachers specializing in Physics, Chemistry and Biology—, currently being trained in scholastic scientific research. The methodology used in this research was the technique of Natural Semantic Networks (Valdez, 1998), a tool that seeks to identify the influence of culture in the psychological construction of identities. The study concludes that the teachers in the study displayed traditional, positivist beliefs on science. They conceive a science of algorithmic and formal teaching, based on the transmission of concepts and the construction of definitive, static, true, and absolutescientific thinking